Alpinone exhibited immunomodulatory and antiviral activities in Atlantic salmon. Issue 74 (March 2018) - Valenzuela, Beatriz; Rodríguez, Felipe E.; Modak, Brenda; Imarai, Mónica
Abstract: In this study, we seek to identify flavonoids able to regulate the gene expression of a group of cytokines important for the control of infections in Atlantic salmon ( Salmo salar ). Particularly, we studied the potential immunomodulatory effects of two flavonoids, Alpinone and Pinocembrine, which were isolated and purified from resinous exudates of Heliotropium huascoense and Heliotropium sinuatum, respectively. The transcript levels of TNF-α and IL-1 (inflammatory cytokines), IFN-γ and IL-12 (T helper 1 type cytokines), IL4/13A (Th2-type cytokine), IL-17 (Th17 type cytokine) TGF-β1 (regulatory cytokine) and IFN-α (antiviral cytokine) were quantified by qRT-PCR in kidneys of flavonoid-treated and control fish. We demonstrated that the administration of a single intramuscular dose of purified Alpinone increased the transcriptional expression of five cytokines, named TNF-α, IL-1, IFN-α, IFN-γ and TGF-β1 in treated fish compared to untreated fish. Conversely, administration of purified Pinocembrine reduced the transcriptional expression of TNF-α, IL-1 and IL-12 in the kidney of treated fish. No other changes were observed. Interestingly, Alpinone also induced in vitro antiviral effects against Infectious Salmon Anaemia virus. Results showed that Alpinone but not Pinocembrine induces the expression of cytokines, which in vertebrates are essential to control viral infections while Pinocembrine reduces pro-inflammatory cytokines. Altogether results suggest that Alpinone is a good candidate to be further tested as immunostimulant and antiviral drug. Highlights: Alpinone and Pinocembrine were isolated and purified from resinous exudates of Heliotropium. Immune effects of Alpinone and Pinocembrine were studied in the kidney of Atlantic salmon. Pinocembrine reduced in vivo the expression of TNF-α, IL-1, IL-12, IL4/13A and TGF-β1. Alpinone increased in vivo the expression of TNF-α, IL-1, IFN-α, IFN-γ and TGF-β1. Alpinone showed in vitro antiviral activity against Infectious Salmon Anaemia virus.